ANALYSIS OF THE DETERMINANTS OF THE INCIDENCE OF GOUT (URIC ACID) DISEASE FACTORS THAT AFFECT JOINT HEALTH IN INDRA JAYA SUB-DISTRICT IN 2023 - Ismi, Rozatul; Mhd. Hidayattullah; Kala, Pasyame Rembune (Transpublika Publisher, 2024)
The incidence of gout in the world is estimated at 47.2% which varies in various populations spread throughout the world. The prevalence of gout in the population aged> 15 years according to the district of Aceh Jaya based on the highest doctor's diagnosis is in several gampong (12.62%), therefore the Indarajaya Health Center working area was chosen as the location of this study. This study aims to determine the predictors of gout in communities in coastal areas. This study used a case-control study design. The population in this study were people living in coastal areas of the Indra Jaya Health Center working area with a total sample of 106 samples (53 cases and 53 controls). Sampling using a simple random sampling technique. Data collection using a questionnaire and the data that has been collected is statistically analyzed using the chi-square test at a confidence level of 95% (α = 0.05) which aims to analyze predictors of uric acid. The results showed that genetic factors with a value of (p = 0.004: OR = 3.559: CI = 1.483-8.539) and purine consumption patterns with a value of (p = 0.02: OR = 3.103: CI = 1.162-8.288). It can be concluded that genetic factors and purine consumption patterns are predictors or risk factors for the incidence of gout in coastal communities in the Indrajaya Health Center working area. We recommend that coastal communities limit food.